ANALISIS PENGARUH PENGELUARAN PEMERINTAH, PENANAMAN MODAL DALAM NEGERI, DAN PENANAMAN MODAL ASING TERHADAP PRODUK DOMESTIK BRUTO DI INDONESIA PERIODE 2000–2020 - Tamba, Andrean V.; Purba, Martin Luter; Sihotang, Jusmer (Universitas HKBP Nommensen, 2023)
The aim of this research is to elucidate the influence of government expenditure, domestic investment, and foreign investment on the Gross Domestic Product (GDP) in Indonesia. This research employs an explanatory research type, utilizing a quantitative approach with secondary data. The focus of this research is the development of the Gross Domestic Product in Indonesia from 2000 to 2020. Linear multiple regression analysis is utilized for data analysis in this study. The result of the F-test indicates that government expenditure, domestic investment, and foreign investment collectively significantly affect Indonesia's Gross Domestic Product. Partially, government expenditure, domestic, and foreign investments have a positive impact on GDP; however, only government expenditure exerts a positive effect, while domestic and foreign investments have a negative influence. Based on these data analyses, the government should pay more attention to the realization of government expenditure to exert a more notable effect on the Gross Domestic Product, and also maintain the stability of investment, both domestic and foreign, to support future government planning with the available capital.